EFFECTS OF VARIOUS GRINDING AIDS DOSAGE ON COMMINUTION EFFICIENCY AND CEMENT CHARACTERISTICS - Hojjat Hosseinzadeh Gharehgheshlagh; Sajjad Chehreghani; Behnam Seyyedi (Rudarsko-geološko-naftni Zbornik, 2023)
Grinding aids are materials that are added to cement mixtures to improve the characteristics of the cement or increase the efficiency of the milling systems or both in the clinker grinding (finish grinding) stage. In this study, the effects of four grinding aids (Triisopropanolamine based (TIPA), Triethanolamine based (TEA), Hydroxylamine based (HA), and Calcium nitrate based (CN) grinding aids) in the clinker grinding process were evaluated on the essential characteristics of the produced cement: namely specific surface area (Blaine number), compressive strength of concrete, and the comminution efficiency-retention time (energy saving) at four different dosage levels. In the first step, the grinding time required to reach the Blaine number of the investigated Cement type (S-OPC: Studied Ordinary Portland Cement) was obtained as 69.75 minutes by kinetic grinding tests. Afterward, 17 laboratory-scale grinding tests were performed utilizing S-OPC cement and four grinding aids at four different doses of 0.02%, 0.05%, 0.08% and 0.11 %. The results indicated that the TIPA-0.11 (Triisopropylamine compound at a dosage level of 0.11%), with a Blaine value of 4069 cm2/g, and grinding efficiency of 19%, had the most significant effect on the fineness and comminution efficiency. Furthermore, the concrete samples produced from all the grinding aids were tested for their compressive strength at 2, 7, and 28 days. The results showed that compared to control samples, the highest growth of compressive strength were on day 2 and 7 for TIPA-0.11 samples with values of 37.08% and 32.44%, respectively. Meanwhile, the highest increase of compressive strength was after 28 days for TIPA-0.11 samples with a 22.14% increase.